LIS pre-professionals' perspectives towards library user education: A comparative study between three universities in Greater China. (September 2020) - Allard, Bradley; Lo, Patrick; Liu, Qianxiu; Ho, Kevin K.W.; Chiu, Dickson K.W.; Chen, Joyce C.C.; Zhou, Qingshan; Jiang, Tianjin
Although the perceptions of library user education of academic libraries has been studied in a general context, specific studies on perspective of library and information science students are relatively few, especially in the context of Asia. Filling this research gap is particularly important because it affects the experiential learning of these pre-professionals, and shapes future library user education directions. As such, this study aims at understanding and comparing the views and perceptions of library user education programs in Greater China from the perspective of library and information science students. A total number 305 questionnaire survey responses were collected from three different universities in Greater China, namely: The University of Hong Kong (HKU), National Taiwan Normal University (NTNU), and Peking University (PKU). Results from this survey study reveal high evaluations of library user education programs and library user education librarians as a whole, as well as possible ways for librarians to better promote such programs. Such ratings are attributed to findings from previous studies on why students choose librarianship as a career, as well as the importance of experiential learning embedded in the Library and Information Science programs at each university. Findings of this study also suggest that as pre-professionals (soon-to-be professional librarians), these student respondents recognize the values behind library user education as an important part of their overall learning practices. Results from this study will be useful in identifying how future library professionals in Greater China perceive library user education programs, and librarians – therefore potentially helping librarians improve the delivery of these services.